Intrahepatic cholestasis of pregnancy resistant to both therapeutic plasma exchange and albumin dialysis. Issue 2 (8th February 2022) - Lia, Massimiliano; Berg, Thomas; Weydandt, Laura Christina; Stepan, Holger
Abstract : Intrahepatic cholestasis in pregnancy (ICP) represents, depending on its severity, a serious risk for the fetus. Those cases with unusually high bile acid levels may be resistant to pharmaceutical treatment and can be treated with plasma exchange or albumin dialysis. However, the success rate of these therapeutic options and the factors influencing therapeutic response are unknown. Furthermore, if these options fail to improve ICP and serum bile acid levels are very high (>200 μm/L), there are no clear recommendations when delivery should be planned. Here, we report a patient with severe ICP resistant to both therapeutic plasma exchange and albumin dialysis. Caesarean section was performed at 32 weeks of gestation followed by rapid remission of ICP.